Inexpensive water soluble methyl methacrylate-functionalized hydroxyphthalimide: variations of the mycophenolic acid core for selective live cell imaging of free cysteine. Issue 7 (17th February 2021) - Lee, Woohyun; Yudhistira, Tesla; Youn, Wongu; Han, Sol; Halle, Mahesh B.; Choi, Jae Hyuck; Kim, Youngsam; Choi, Insung S.; Churchill, David G.
Abstract : We report a new fluorescent probe (Myco-Cys ) for live cell cysteine imaging. Myco-Cys contains a methacrylate cleavable pendant group that preferentially reacts with cysteine over homocysteine and glutathione to afford a "turn-on" response. Abstract : Evident from numerous studies, cysteine plays a crucial role in cellular function. Reactions with analyte also enables for molecular recognition to adhere to molecular therapeutic potential; integration between synthetic probes therefore allows for a potentially deep therapy-related interogation of biological systems (theranostics). The development of molecular cysteine probes with extremely accurate detection is still a key challenge for the field. The development of water-soluble organic molecular fluorescent probes able to efficiently distinguish common biothiols such as cysteine (Cys), homocysteine (Hcy) and glutathione (GSH) by chemical recognition means i.e. by (binding, cleavage) in biological systems is a greatly sought research challenge due to the similarity of the small sulfhydryl-containing species. Herein, we have developed a water-soluble and highly cell viable fluorescent organic molecule (log P = 0.82) for the selective detection of cysteine. The probe (Myco-Cys ) shows a "turn-on" response with the cleavage ester linkage of the methacrylate as cysteine is encountered in solution. The probe shows strong fluorescence enhancement (16.5-fold) when treated with Cys (1 equiv., 10 μM) compared to closely related species such as amino acids, including HCy/GSH, and the limit of detection was determined as 45.0 nM. DFT calculations helped confirm the photomechanism of Myco-Cys . Furthermore, the sensing ability of the probe was demonstrated by living cell assays through the use of confocal fluorescence microscopy. Myco-Cys could selectively detect cysteine among biothiols. Myco-Cys was able to monitor the cysteine level, apart from the oxidative stress present in the form of H2 O2 in A549 cells.